已知a^2+2ab+b^2=0,求代数式a(a+4b)-(a+2b)(a-2b)

2025-02-24 02:21:42
推荐回答(5个)
回答1:

a^2+2ab+b^2=0,
(a+b)^2=0 所以可得:a+b=0
a(a+4b)-(a+2b)(a-2b)
=a^+4ab-a^2+4b^2
=4b(a+b)
=0

回答2:

第一步:因a²
+2ab+b²
=0
推出(a+b)²
=0
,也就是a+b=0
第二步:a(a+4b)-(a+2b)(a-2ab)=(a²+4ab)-(a²-4b²)=4ab+4b²
=4b(a+b)
因第一步已推出a+b=0
所以4b(a+b)=0

回答3:

由于a^2+2ab+b^2=0,
得 (a+b)^2=0;
即a=-b
a(a+4b)-(a+2b)(a-2b)=-b*(3b)-b*(-3b)=-3b^2+3b^2=0

回答4:

由已知得a+b=0,所以a^2+4ab-a^2+4b^2=4b(a+b)=0

回答5:

a^2+2ab+b^2=0
(a+b)^2=0
a+b=0
a=0
b=0
a(a+4b)-(a+2b)(a-2b)=0